2023
DOI: 10.2174/1389201023666220921125258
|View full text |Cite
|
Sign up to set email alerts
|

Chia Seeds Oil Suppresses the Resistance of Hepatocellular Carcinoma Cells to Liposomal-doxorubicin and Upregulates the Tumor Suppressor miRNAs

Abstract: Background: Chia seed is an oil-seed of multiple biological activities. Doxorubicin is an effective chemotherapy for liver cancer. Resistance and adverse effects are doxorubicin limitations. Objective: This study aimed to investigate the effect of chia seeds oil (CSO) on the resistance of HepG2 cells to liposomal-doxorubicin (DOX). Methods: The objective were investigated through measuring cytotoxicity, doxorubicin-metabolizing enzyme Cytochrome P450 3A4 (CYP-3A4), multidrug resistance-associated protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Rosas-Ramirez et al, reported the effects of chia oligosaccharide mucilages in decreasing proliferation of HepG2 cells (14). Tawfik, S. A., et al showed that the Salvia hispanica increased the sensitivity of HepG2 cells to the chemotherapy agent doxorubicin (38). Our results are support of those previous studies regarding the inhibitory effect of Salvia hispanica on HepG2 cell proliferation.…”
Section: Discussionsupporting
confidence: 91%
“…Rosas-Ramirez et al, reported the effects of chia oligosaccharide mucilages in decreasing proliferation of HepG2 cells (14). Tawfik, S. A., et al showed that the Salvia hispanica increased the sensitivity of HepG2 cells to the chemotherapy agent doxorubicin (38). Our results are support of those previous studies regarding the inhibitory effect of Salvia hispanica on HepG2 cell proliferation.…”
Section: Discussionsupporting
confidence: 91%